'I had the luxury . . .': Organizational breastfeeding support as privatized privilege. (July 2014) - Turner, Paaige K; Norwood, Kristen
To make the combination of breastfeeding and work feasible, women who return to work full time in the USA need some measure of organizational breastfeeding support. Yet, many organizations do not have lactation policies in place, co-worker and supervisor communication can be discouraging, and predominant cultural Discourses in the US position breastfeeding at odds with organizational values, often requiring women to define and negotiate support themselves. Drawing upon Structuration Theory, we analyzed interviews conducted with US women who breastfed and worked to illuminate the meanings they held for breastfeeding and organizational breastfeeding support and how those meanings challenge and reproduce social systems that make breastfeeding and working a potentially difficult combination. We argue that their construction of breastfeeding support as a privatized privilege re/produces cultural Discourses that marginalize women's bodies in organizations. In order to engender support for all bodies that challenge the borders between public/private, feminine/masculine and personal/professional, meanings must be changed at both macro and micro levels of communication.